2019
DOI: 10.14246/irspsda.7.2_143
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Choice Behaviour towards Docked and Dockless Shared Bicycles based on User Experience

Abstract: The major cities of China have experienced massive growth in the number and usage of dockless shared bicycle systems, such as Mobike and Ofo, which have replaced the traditional docked bicycle systems that are heavily regulated by local governments. However, docked bicycle systems are still in operation, especially in small and medium-sized cities that have docked shared bicycle systems run by the local government. This study aims to reveal the user choice behaviours for these two shared bicycle systems from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This positive effect is most evident in the northern and southern suburban. Both docked and dockless bike-sharing play important roles in integrating with public transport, especially for commuting purpose on weekdays in suburban areas (Li et al, 2019b;Ma et al, 2018a;Yang et al, 2016). Because of the popularity of dockless bike-sharing, many people who ignored docked bike-sharing before gradually start to accept docked bike-sharing.…”
Section: Spatial Feature Of Variable Coefficientsmentioning
confidence: 99%
“…This positive effect is most evident in the northern and southern suburban. Both docked and dockless bike-sharing play important roles in integrating with public transport, especially for commuting purpose on weekdays in suburban areas (Li et al, 2019b;Ma et al, 2018a;Yang et al, 2016). Because of the popularity of dockless bike-sharing, many people who ignored docked bike-sharing before gradually start to accept docked bike-sharing.…”
Section: Spatial Feature Of Variable Coefficientsmentioning
confidence: 99%
“…Previous research has demonstrated the impact of risk perception on people's decision and behavior (Li & Tang, 2019;Reisinger & Mavondo, 2005). The destination choice behavior is also related to risk perception (Han et al, 2020;Sinha & Nair, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Their study indicated that underperforming stations had emerged in the case of Seoul City as a result of the indiscriminate deployment of stations in the early stages of introducing shared bicycles. Lin and Yang (2011) and Chen et al (2015) also argued that station location decisions are key to the success of shared services. Therefore, it can be seen that for PMS to succeed, it is very important to find the station locations and service areas considering the demand.…”
Section: Review Of Related Researchmentioning
confidence: 99%